2012
DOI: 10.1590/s0100-29452012000100039
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do estresse salino na absorção de nutrientes em mangueira

Abstract: Avaliou-se o efeito do estresse salino sobre a massa seca, a absorção e o transporte de nutrientes nas mangueiras 'Haden', 'Palmer', 'Tommy Atkins' e 'Ubá' enxertadas sobre 'Imbu'. Foi utilizada solução nutritiva de Hoagland modificada em sistema hidropônico estático aerado, contendo: 0; 15; 30 e 45 mmol L-1 NaCl. A massa seca de raízes, caule do porta-enxerto e caule da cultivar copa, bem como das folhas, foi reduzida em concentrações a partir de 15 mmol L-1 NaCl. Ocorreu redução de N, P, K+, Ca+2 e Mg+2 nas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…curcas plants also showed decreased effective PSII quantum yield due to salinity increase in consequence of the negative effect of salt stress on the photosynthesis apparatus. Actually, several studies involving different plant species such as Ricinus communis L. (Li et al, 2010) and Mangifera indica L. (De Lucena et al, 2012) have shown that the PSII effective quantum yield progressively decreases when the salt content in soil solution increases.…”
Section: Morphologicalmentioning
confidence: 99%
“…curcas plants also showed decreased effective PSII quantum yield due to salinity increase in consequence of the negative effect of salt stress on the photosynthesis apparatus. Actually, several studies involving different plant species such as Ricinus communis L. (Li et al, 2010) and Mangifera indica L. (De Lucena et al, 2012) have shown that the PSII effective quantum yield progressively decreases when the salt content in soil solution increases.…”
Section: Morphologicalmentioning
confidence: 99%
“…In Brazil, the use of mango cultivars showing high level of basal resistance against C. fimbriata infection has been the most effective control strategy mainly because of a failure in the use of pesticides (Ribeiro 2005;Rossetto et al 1996;Viégas 1960). Some mango cultivars showing greater resistance to mango wilt are at the same time very sensitive to salt stress (Lucena et al 2012). For example, Tommy Atkins and Ubá cultivars, considered to be resistant to mango wilt (Araujo et al 2014;Rossetto et al 1996), are tolerant and sensitive, respectively, to salt stress (Lucena et al 2012).…”
mentioning
confidence: 99%
“…Some mango cultivars showing greater resistance to mango wilt are at the same time very sensitive to salt stress (Lucena et al 2012). For example, Tommy Atkins and Ubá cultivars, considered to be resistant to mango wilt (Araujo et al 2014;Rossetto et al 1996), are tolerant and sensitive, respectively, to salt stress (Lucena et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations